Fostering of Entrepreneurship Competencies and Entrepreneurial Intentions in a Weak Ecosystem - Marina Solesvik; Paul Westhead (Foresight and STI Governance)
This exploratory study conducted in the transitional context of Ukraine explores whether students drawn from a supportive entrepreneurship education (EE) reported higher intensity of entrepreneurial intention (IOEI) than students that did not participate in EE.  Further, this study explores what specific competencies honed within a supportive EE are associated with students reporting high IOEI. Guided by competency theory, two hypotheses were tested with regard to a representative sample of 125 business EE students, and a further 64 engineering students that had never participated in EE.  EE students drawn from a supportive educational entrepreneurial ecosystem were found to be associated with significantly higher IOEI.  With regard to 13 competencies honed by EE, it was found that only three competencies (the ability to identify high quality opportunities, computer literacy, and networking) were significantly albeit to a weak degree associated with higher IOEI.  Additional studies are warranted in several former Soviet Union contexts to provide a rigorous evidence base to guide resource allocation decisions of the government with regard to supporting EE and entrepreneurial ecosystems.  This exploratory study relating to the sample of students in one entrepreneurial ecosystem in the Ukraine does not provide conclusive evidence for the government to more proactively support the educational entrepreneurial ecosystem with regard to its current content and delivery.